An Overview of Multi-Microcontroller Bus Synchronization for Simultaneous Operation of the Microcontrollers (International Journal of Engineering and Computer Science, 2015)
Now a day’s embedded systems are more complex and complicated as compared to the old one. Low power microcontrollers are limited to a specific task. But current time demand is data specific which requires more data processing. Re configurability is also an interesting feature of current time embedded system. So we have to develop a system that is easily re configurable as per our requirement. Cost is also a design factor; we have to develop a system that its cost will not increase. High power microcontrollers are able to process higher data at a higher speed taking higher amount of power. But when our task is limited to power, cost; high power microcontrollers can’t be used. High power microcontrollers become problematic for the battery operated embedded systems where power backup is limited.  To overcome this problem we are developing Multi-microcontroller System on Programmable Chip (MMSoPC). Synchronization is a key problem in multi-microcontroller systems to operate simultaneously. To synchronize the buses of the microcontrollers, network on chip (NoC) is the solution. Local system buses are connected to a common system bus i.e. global system bus. Global buses are externally available to the outside for different interfacing of various components/peripherals etc. So there is a need of synchronization of local system buses to the global system bus.